The role of technological changes in labor markets transition: From historical to modern perspective - Teona Eliashvilli (Transformation, Integration and Globalization Economic Research (TIGER), 2021)
Computing capability continues to expand at a breakneck pace. New technologies are permeating the economy at an increasing rate. Machines are becoming capable of performing jobs previously solely performed by people due to digitization and automation. Manufacturing processes and organizations are evolving, and new goods, services, and business strategies are emerging. These developments have significant ramifications for labour markets. The changing nature of work in the twenty-first century, the growing gap between skill supply and demand sparked a lively discussion regarding the role of technology in influencing future labour markets and general economic well-being. From historical to current perspectives, this working paper gives data on the effects of technology changes on labour markets. More particular, it seeks to address how technology advancements will transform the current labour market structure. The study uses the descriptive data analysis approach, based on academic literature and quantitative assessments of available data, in order to forecast the impact variables that may influence future labour market results. One of the paper's significant findings is that the main problem will not be the statistics. It refers to the employment structure and the resulting requirement for supply-side modifications to satisfy the shift in demand between occupations and sectors. Finally, this article discusses the policy consequences of systemic changes that first represent the functioning of education and training facilities, their linkages with labour market restrictions, and corporate methods to teach individuals with new skills.
Keywords: 330; Technology; Technological Change; Labour Markets; Skill-Biases; Innovation; Technology Diffusion; Future Work